(untitled) (International Seven Journal of Multidisciplinary, 2023)
Artificial intelligence (AI) is playing a transformative role in the fashion industry, changing how designers create, produce, and sell clothing. Tools such as DALL·E, MidJourney, and DeepDream enable the generation of sophisticated designs from textual descriptions, expanding creative possibilities and accelerating the design process. Additionally, software like CLO 3D and Browzwear revolutionizes clothing modeling and production, reducing the need for physical prototypes and minimizing material waste. Brands such as H&M, Nike, and Adidas already use AI to predict trends, optimize inventory, and tailor collections to consumer preferences. AI not only improves production efficiency but also opens new possibilities for personalization and inclusivity, creating designs adapted to different body types. The technology is being employed at various stages of the supply chain, from creation to distribution, offering sustainable solutions for the industry. With the growing adoption of AI, fashion is becoming more dynamic and personalized, reflecting a digital future where collaboration between humans and machines is essential. Research highlights that AI can enhance creativity but also presents challenges that require careful integration and continuous adaptation to the creative process.